Formulasi Sediaan Salep Ekstrak Etanol Daun Cengkeh (Syzygium aromaticum folium) Dengan Variasi Konsentrasi Basis Hidrokarbon - Jayanti Djarami; Aulia Debby Pelu; Dwi Sintya Karubaba (JURNAL FISIOTERAPI DAN ILMU KESEHATAN SISTHANA, 2020)
Clove plant (Syzygium aromaticum. L) Is one of the plants known by the people in Bula village as a traditional medicine the leaves of cloves (Syzygium aromaticum folium) are often used as an alternative to cure stiff and rheumatic diseases such as causing pain due to excessive activity, so that it can be used as an active ingredient in making ointments The purpose of this study was to identify the chemical content of clove leaves (Syzygium aromaticum folium) from Bula village and to formulate a good and stable clove leaf ethanol extract ointment (Syzygium aromaticum folium) using a ratio of variations in the concentration of the Hydrocarbon Base. This research method is experimental which was carried out using a combination base of vaseline album: cera alba from three different formulations with a concentration ratio of F1 (76%: 10 %), F2 (71%: 15%), F3 (66%: 20%), each formulation contains 10% ethanol extract of clove leaf (Syzygium aromaticum folium). Evaluation of ointment preparations was carried out after 1 week of storage; evaluation tests included organoleptic tests, homogeneity tests and pH tests. The results showed that the ointment preparations F1 (76%: 10%) met the requirements for a good and stable ointment, while F2 (71%: 15%), and F3 (66%: 20%) did not meet the requirements for a good and stable ointment.